Influence of left ventricular unloading on pediatric post-cardiotomy veno-arterial extracorporeal life support outcomes - Meani, Paolo; Lorusso, Roberto; Kowalewski, Mariusz; Isgrò, Giuseppe; Cazzaniga, Anna; Satriano, Angela; Ascari, Alice; Bernardinetti, Mattia; Cotza, Mauro; Marchese, Giuseppe; Ciotti, Erika; Kandil, Hassan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background. The effectiveness of veno-arterial extracorporeal life support (V-A ECLS) in treating neonatal and pediatric patients with complex congenital cardiac disease (CHD) and requiring cardio-circulatory assistance is well known. Nevertheless, the influence of left ventricle (LV) distension and its countermeasure, namely LV unloading, on survival and clinical outcomes in neonates and children treated with of V-A ECLS needs still to be addressed. Therefore, the study aim is to determine the effects of LV unloading on in-hospital survival and complications in neonates and children treated with V-A ECLS. Methods. The clinical outcomes of 90 CHD pediatric patients under 16 years of age supported with V-A ECLS for post-cardiotomy cardiogenic shock (CS) were retrospectively reviewed in relationship with the presence or absence of an active LV unloading strategy. Results. The patient cohort included 90 patients (age 19.6±31.54 months, 64.4% males), 42 of whom were vented with different techniques (38 with atrial septostomy or left atria cannula, 2 with cannula from LV apex, 1 with intra-aortic balloon pump and 1 with pigtail across aortic valve). Unloading strategy significantly increased the in-hospital survival (OR= 2.74, CI 1.06-7.08; p= 0.037). On the contrary, extracorporeal cardio-pulmonary resuscitation decreased the related survival (OR= 0.323, CI 1.09-0.96; p= 0.041). The most common complications were infections (28.8%), neurological injury (26%) and bleeding (25.6%). However, these did not differently occur in venting and no-venting groups. Conclusion. In pediatric CHD patients supported with V-A ECLS for post-cardiotomy CS, the LV unloading strategy was associated with increased survival.